Worldviews and Science. - Stenmark, Mikael (Zygon: Journal of Religion & Science, 2024)
The increasing number of individuals who lack religious faith or self-identify as nonreligious in certain parts of the world necessitates a shift in the science–religion dialogue and a change of some key categories and notions. This shift, I argue, implies the expansion of the science–religion dialogue into a science–worldview dialogue, so the core question becomes the relevance of science for the formation, revision, and rejection of both religious worldviews (such as Buddhism, Christianity, and Islam) and secular worldviews (such as scientific naturalism, liberal naturalism, and secular humanism). I begin by explaining what worldview studies are and why refocusing from science and religions to science and worldviews is important. I then identify the main ways of relating science and worldviews in a new typology and provide examples for each.